The Actual Status of Pupils' Support Policies in Vietnamese Ethnic Semi-Boarding Schools - Hanh, Vuong Thi Phuong; Giang, Tran Thi Ha; Thanh, Tran Van; Dong, Nguyen Nhu; Thu, Tran Thi Hoai; Hanh, Vuong Hong (Journal of Posthumanism, 2025)
One of the subjects that the Vietnamese government focuses and pays attention to developing is ethnic minority pupils, as stated in the Vietnamese Education Law 2019. In order to prioritize funding for education and training in ethnic minority communities, particularly for pupils attending ethnic semi-boarding schools, the government has mandated the creation and implementation of a number of systems and regulations. This program seeks to advance educational equality while addressing the educational requirements of children from ethnic minorities. In addition to the advantages and beneficial effects the policy has had in the past, the process of putting it into practice has shown challenges and restrictions that must be addressed and modified to meet new demands. In order to provide a scientific foundation for suggesting solutions and recommendations to the National Assembly, the Government, and relevant Ministries and sectors to amend, supplement, and promulgate policies appropriate for the current context of educational innovation, this article uses a combination of survey investigation through questionnaires, in-depth interviews with managers, teachers, parents, and pupils of ethnic semi-boarding schools, and retrospective research of documents.